Colonial world-making in future technological landscapes: a qualitative comparative case study of the Sophia the Robot and Miquela Projects - May, Abigail (Department of Political Studies, 2023)
Future technologies are being produced by private actors in projects promising radical societal changes. Little attention is given to the intention of these private actors. This increases the risk of missing the ways in which private political and economic interests shape future technological imagining. From Jeff Bezos floating space coloniesto Mark Zuckerberg's reality bending ‘metaverse', private companies envision futures that will be far better than present society. However, factors that caused the need for societal transformation are being reworked into the imaginings of future landscapes promising. Through a comparative case study analysis of the robot projects of Sophia the Robot and Miquela Sousa, the argument presented in this research study is thatthe improved and inspiring future landscapes each robot project presents cannot be achieved. This is because the ideological framing of each project replicates the logic of modernity, which functions on structures of oppression. By applying colonial and modern examples from the past and present, this study illustrates the ways in which systems of oppression – such as white supremacy and enslavement- are reproduced in the imaginings of the future in private actors' technological projects as well as the technologies itself.